Intervenção domiciliar e envolvimento paterno: efeitos em famílias de crianças com síndrome de Down - Silva, Nancy Capretz Batista da (2011)
The family is of fundamental importance in child development. Although neglected in many studies, the father is a unique contributor to his child s development, but remains absent from early intervention programs. This study aimed to determine the effect of a home-based intervention for fathers on their child s development, the interaction of both parents with their child, and the effects on home envorinment and on stress, depression, level of coping, parental and marital satisfaction, perceptions of family functioning and social support and empowerment of both parents. Six families of children with Down s syndrome, between 1 and 2 years of age had their children s development evaluated using the Operationalized Portage Inventory, in two São Paulo in country cities. The Questionnaire for the Characterization of the Family System was used to capture demographic information about the families; parts C and D of the General Guide of Transcription of Interview Data to evaluate the participation of fathers and grandparents; the Interview for the Characterization of Brazilian Fathers Role in the Education of a Child with an Intellectual Disability to evaluate fathers involvement; HOME Inventory to assess stimulation ofered to the child in the home environment; QRS-F and Lipp s Inventory of Stress Symptoms to measure parents stress; Beck s Depression Inventory to assess the existence and the level of depression; FACES III to evaluate the perception of family functioning; Coping Strategies Inventory to assess the level of coping; Social Suport Questionnaire to evaluate the perception of social suport; PSOC to assess parental satisfaction; Scale of Marital Satisfaction to assess marital satisfaction and FES to evaluate parents empowerment. In order to observe fatherchild, mother-child and father-mother-child interactions, it was used the Protocol for Categorizing the Analysis of Filmed Interactions, the Definitive System of Observational Categories and a Protocol for the Evaluation of Dyadic/Triadic Interaction. It was observed that all children had developmental delays. Parents asessment indicated: low levels of stress related to the child s presence, absence of stress among fathers, stress among all the mothers, high levels of self-esteem and empowerment, one father with depression, high levels of cohesion and adaptability, the use of various coping strategies, wide social networks and satisfaction with social support and good marital satisfaction among couples. In addition, all offered home environments that stimulated and supported their children, and family interactions were satisfatory, although they differed in some respects between fathers and mothers and in dyads and triads. The training activities conducted by the fathers, based on the Portage Inventory contributed to the development of new repertories in their children, positive behaviour in interactions were more frequent over time and a decrease in indices of stress among the mothers. The other parents charateristics assessed didn t alter generally during the families participation in the study. The stimulation and support in the home environment became better or worse depending on the family. The relation between some results and research in this field is discussed. It was concluded that early intervention programs should abandon the child-centered model to adopt a familycentered model, in which fathers are an important parent for family functioning and for child development.